The effect of architecture on the mechanical properties of Mg–3Al–1Zn Rods Containing Hard Al Alloy Cores. (15th March 2015) - Feng, Bo; Xin, Yunchang; Hong, Rui; Yu, Huihui; Wu, Yang; Liu, Qing
Abstract : Three types of Mg–3Al–1Zn (AZ31) rod containing different architectures of hard Al alloy core (single-fiber, three-fiber and circular-tube cores) are fabricated using extrusion. Our results show that the three types of core architecture under the same volume fraction generate very different hardening effects during compression along the extrusion direction (ED), in contrast to similar hardening effects during tension along the ED. The core architectures also affect the microstructure and texture of the Mg alloy sleeve.